Kontrola cene električne energije in plina - Pirnat, Rajko (Podjetje in delo, 2022)
The author analyses the admissibility of price control measures to fix the maximum price of electricity and gas. The author finds that the measure as provided in the Decree on determining electricity prices is contrary to the Directive on common rules for internal market for electricity, while this cannot be said for gas price control. The author also argues that constitutionally coherent interpretation of Article 14 of the Price Control Act requires that the government grants suppliers adequate compensation for costs of supply and return on investment. As criteria for calculating the compensation, the author proposes the Altmark criteria.
Keywords: cena električne energije; cena plina; dobava električne energije; dobava plina; electricity; električna energija; Energetika; natural gas; Oblikovanje cen; price control measure; ukrep kontrole cen; zemeljski plin